Intraocular pressure and myopia progression in Chinese children: the Anyang Childhood Eye Study. Issue 3 (1st June 2018) - Li, Shi-Ming; Iribarren, Rafael; Li, He; Kang, Meng-Tian; Liu, Luoru; Wei, Shi-Fei; Stell, William K.; Martin, Gabriel; Wang, Ningli
Abstract : Purpose: To explore the relationship between intraocular pressure (IOP) at baseline and myopia progression in Chinese children from the Anyang Childhood Eye Study. Design: Prospective school-based cohort study. Methods: A total of 1558 grade 7 students completed the entire 2-year study. Ocular biometry, cycloplegic refractions and pneumotonometry were performed. Three years of follow-up have been completed for the children aged 12 years. The refractive groups and the tertiles of IOP were assessed by analysis of variance, to look for differences in mean values of spherical equivalent and IOP, respectively. Results: The children's mean baseline IOP was 15.87±3.42 mm Hg. Mean IOP was significantly higher in girls by 0.57 mm Hg (p=0.024). In the whole sample, there was a mean change in spherical equivalent of −1.05 D over 2 years. The baseline IOP was 15.69 mm Hg in those progressing 1 D or more vs 16.09 mm Hg for those progressing <1 D (p=0.022). In the myopic group, myopes progressing >1 D had mean IOP of 15.94 vs 16.42 mm Hg for those myopes progressing 1 D or less (p=0.024). Conclusions: In this sample of Chinese children, myopia progression over 2 years was inversely related to IOP, suggesting that IOP had essentially no relationship with myopia progression in school children. The lower IOP in progressing myopic eyes may indicate more compliant sclerae.